The evaluation performance of letter-based techniques on text steganography method - Ismail, Azizan; Din, Roshidi; Mustapha, Aida; Utama, Sunariya (Institute of Advanced Scientific Research, 2018)
The implementation of steganography as information hiding in research area is able in covering hidden message in text, image, audio and video. This paper focuses on the implementation of development steganography in text domain named text steganography. Mostly, the researcher utilize the text steganography technique named feature-based technique that covers a hidden message based on the uniqueness of letters. One of the technique in feature-based is letter-based technique that is able to hide the hidden message in a language that uses A-Z letters. This paper focuses on the three techniques of letter-based text steganography that have a similar implementation process in covering the hidden message. The three techniques are evaluated using some parameters to obtain the size bit ratio, loading time and validation performance. This parameter used in order to notice that the process of covering the hidden message could be influence capacity of text, the length of time consuming and determine the quality performance in term of validation approach.